Inhibition of Osteoclast Generation: A Novel Function of the Bone Morphogenetic Protein 7/Osteogenic Protein 1 - Thomas Maurer; Gerald Zimmermann; Susanne Maurer; Sabine Stegmaier; Christof Wagner; G. Maria Hänsch (Hindawi Limited, 2012)
Monocytes have the potential to differentiate to either macrophages, dendritic cells, or to osteoclasts. The microenvironment, particularly cytokines, directs the monocyte differentiation. Receptors of NFκB (RANK) ligand, tumor necrosis factor (TNF) α, or interleukin- (IL-) 8 have be identified as inducers of osteoclastogenesis, whereas others, such as IL-10 or transforming growth factor (TGF)ß inhibit osteoclast generation or induce differentiation towards a dendritic cell type. We now describe that bone morphogenetic protein (BMP) 7/osteogenic protein- (OP-) 1 inhibited the differentiation of human CD14+ monocytes to osteoclasts. In the presence of BMP7/OP-1 the transcription factors c-Fos and NFATc1, though upregulated and translocated to the nucleus in response to either RANKL or IL-8, did not persist. In parallel, MafB, a transcription factor expressed by monocytes and required for differentiation to macrophages but inhibiting osteoclast generation, was preserved. Because both persistence of NFATc1 and downregulation of MafB are crucial for osteoclastogenesis, we conclude that BMP7/OP-1 inhibits the generation of osteoclasts by interfering with signalling pathways.